Normative study of SATURN: a digital, self-administered, open-source cognitive assessment tool for Italians aged 50–80 - Giaquinto, Francesco; Assecondi, Sara; Leccese, Giuliana; Romano, Daniele Luigi; Angelelli, Paola (Frontiers in Psychology, 2024)
This study aimed to establish normative data for the Self-Administered Tasks Uncovering Risk of Neurodegeneration (SATURN), a brief computer-based test for global cognitive assessment through accuracy and response times on tasks related to memory, attention, temporal orientation, visuo-constructional abilities, math (calculation), executive functions, and reading speed. A sample of 323 neurologically healthy Italian individuals with Montreal Cognitive Assessment (MoCA) equivalent score ≥ 1 (180 females; average age: 61.33 years; average education: 11.32 years), stratified by age, education, and sex, completed SATURN using PsychoPy, and a paper-and-pencil protocol consisting of the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). Data analyses included: (i) correlations between the total accuracy scores of SATURN and those of MMSE and MoCA; (ii) multiple regressions to determine the impact of sex, age, and education, along with the computation of adjusted scores; (iii) the calculation of inner and outer tolerance limits, equivalent scores, and the development of correction grids. The mean total time on tasks was 6.72±3.24 minutes. Age and education significantly influence the SATURN total accuracy, while sex influences the total time on tasks. Specific sociodemographic characteristics influence subdomain accuracies and times on task differently. For the adjusted SATURN total score, the outer limit corresponds to 16.56 out of 29.00 (cut-off), while the inner limit is 18.57. SATURN significantly correlates with MMSE and MoCA. In conclusion, SATURN is the first open-source digital tool for initial cognitive assessment in Italy, showing potential for self-administration in primary care, and remote administration. Future studies need to assess its sensitivity and specificity in detecting pathological cognitive decline.